Heun-Type Solutions of the Klein-Gordon and Dirac Equations in the Garfinkle-Horowitz-Strominger Dilaton Black Hole Background - Marina-Aura Dariescu; Ciprian Dariescu; Cristian Stelea (Advances in High Energy Physics)
We study the Klein-Gordon and the Dirac equations in the background of the Garfinkle-Horowitz-Strominger black hole in the Einstein frame. Using a SO(3,1)×U(1)-gauge covariant approach, as an alternative to the Newman-Penrose formalism for the Dirac equation, it turns out that these solutions can be expressed in terms of Heun confluent functions and we discuss some of their properties.